Med hvilken rett blir din sigøynerhistorie min fortelling? Om innsamlings- og fortolkningsproblematikk - Dahlsveen, Heidi; Gjærum, Rikke Gürgens; Walløe, Thor-André (Nordic Journal of Art & Research, 2015)
The article explores the stories we choose to tell about others and with what right other people's stories becomes the storyteller's own material. The article discusses the actual collection and interpretation issues when one both is a researcher, facilitator and a storyteller in a project that deals with marginality and vulnerable groups in the community. The ethnographic study article based on the preservation of intangible cultural heritage, generated stories collected from to the gypsies to a storytelling performance "Romfolk-et folk i veien." The purpose of the study was to gather traditional tales, gain insight into representations, expressions and knowledge of who the Gypsies themselves find that they are.